Self-experienced physical workload and risk of breast cancer - Rintala, Pirjo E.; Pukkala, Eero; Paakkulainen, Harri T.; Vihko, Veikko J. (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'The association between the risk of breast cancer and the physical load of work was studied because physical activity may reduce breast cancer risk via hormonal mechanisms. ' ' METHODS ': 'Occupational physical activity was estimated from a self-determined rating [scale 1 (low)-5 (high)] of occupational physical load for 1800 randomly selected women born in 1930-1969. The medians of the ratings were used as occupation-specific indices of occupational physical activity. All 65 occupations with at least 5 ratings, covering 75% of the economically active female population in Finland, were included in further analyses. The occupation-specific numbers of observed and expected cases of breast cancer during 1971-1995 among women born in 1906-1945 (17 986 cases) were grouped according to the index for occupational physical activity. Expected rates were calculated with the social-class-specific population and the entire Finnish female population as reference populations. The relative risks (RR) of breast cancer for categories 3-5, in comparison with categories 1-2 were calculated using Poisson regression models. The occupation-specific mean number of children and mean age at first childbirth were adjusted for. ' ' RESULTS ': 'The RR was lower for occupations in category 5 than for those in categories 1-4, especially in the youngest (25-39 years) age group (RR 0.51, 95% confidence interval 0.44-0.58). Adjustment for social class and reproductive factors raised the RR (95% confidence interval 0.56-0.74) for category 5 in different age strata, all the RR values still being statistically significant. ' ' CONCLUSIONS ': 'The results support the hypothesis that occupational physical activity, if high enough, markedly reduces breast cancer risk.
Keywords: breast cancer; malignant tumor; occupational physical activity; physical workload; risk; self-assessment; self-experienced physical workload; self-report; woman